2001
DOI: 10.1128/iai.69.12.7262-7270.2001
|View full text |Cite
|
Sign up to set email alerts
|

Human Macrophage Gamma Interferon Decreases Gene Expression but Not Replication ofMycobacterium tuberculosis: Analysis of the Host-Pathogen Reciprocal Influence on Transcription in a Comparison of Strains H37Rv and CMT97

Abstract: Mycobacterium tuberculosis is an intracellular pathogen that readily survives and replicates in human macrophages (M⌽). Host cells have developed different mycobactericidal mechanisms, including the production of inflammatory cytokines. The aim of this study was to compare the M⌽ response, in terms of cytokine gene expression, to infection with the M. tuberculosis laboratory strain H37Rv and the clinical M. tuberculosis isolate CMT97. Both strains induce the production of interleukin-12 (IL-12) and IL-16 at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Fractionation studies and immunoblot analyses performed on culture-grown M. tuberculosis found that the Eis protein was distributed throughout the bacterium, including the cell wall and cytoplasm (7). More recent studies have shown that eis is differentially expressed in a clinical strain of M. tuberculosis upon infection of activated human macrophages (4). These results do not suggest a function for the Eis protein or indicate how eis may be regulated.…”
mentioning
confidence: 49%
“…Fractionation studies and immunoblot analyses performed on culture-grown M. tuberculosis found that the Eis protein was distributed throughout the bacterium, including the cell wall and cytoplasm (7). More recent studies have shown that eis is differentially expressed in a clinical strain of M. tuberculosis upon infection of activated human macrophages (4). These results do not suggest a function for the Eis protein or indicate how eis may be regulated.…”
mentioning
confidence: 49%
“…[34][35][36] Studies on gene expression profiles of Mtbinfected human macrophages provided the evidence for the importance of IL-1b and IL-12 in combating Mtb. 37 Importantly, one study identified CCL1, produced from macrophages of TB patients after Mtb stimulation, was involved in host susceptibility to TB. 38 Here, we demonstrated that miR-20a-5p was reduced after mycobacterial infection in vitro and in vivo, which implicates this pathway maybe a potential defense mechanism to promote an effective immune response against infection.…”
Section: Discussionmentioning
confidence: 99%
“…Eis is involved in the survival of mycobacteria during the infection of macrophages (16). It has been shown that Eis is expressed only when the clinical isolate was replicating in activated macrophages (24). However, nothing is known about how Eis mediates its functional activity.…”
Section: Discussionmentioning
confidence: 99%